Forest Restoration as a realization of Indonesian Economic Sustainability - Deltauli Manulang, Euriska; Mego Sundoro, S.E., M.Ec.Dev., Fredericho (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the thematic structure and trends in scientific publications discussing deforestation for future research in this field. Bibliometric analysis (BA) is used to describe the development of deforestation and reveal its bibliometric profile. Data are taken from the Scopus database covering the years 1982 to 2025 by identifying studies on deforestation using the keywords "deforestation" and "Indonesia". This approach ensures a comprehensive database for the study. The number of publications on deforestation in Indonesia has not increased every year. The main contributing countries to this topic are Indonesia, United States, United Kingdom, Malaysia, Netherlands, Australia, Germany, France, Japan, and Singapore. Furthermore, the keyword deforestation in Indonesia is discussed. This study contributes by analyzing deforestation and offering valuable insights into the development of deforestation.